Concomitant Anterior Repair, Preoperative Prolapse Severity, and Anatomic Prolapse Outcomes After Vaginal Apical Procedures. Issue 1 (January 2019) - Nager, Charles W.; Grimes, Cara L.; Nolen, Tracy L.; Wai, Clifford Y.; Brubaker, Linda; Jeppson, Peter C.; Wilson, Tracey S.; Visco, Anthony G.; Barber, Matthew D.; Sutkin, Gary; Norton, Peggy; Rardin, Charles R.; et al.
Abstract : Objective: The aim of the study was to compare anterior and overall prolapse prevalence at 1 year in surgical participants with or without concomitant anterior repair (AR) at the time of sacrospinous ligament fixation (SSLF) or uterosacral ligament suspension (ULS). Methods: This is a secondary analysis of two surgical trials; concomitant AR was performed at surgeon's discretion. Anterior anatomic success was defined as pelvic organ prolapse quantification of prolapse point Ba ⩽0 and overall success was defined as pelvic organ prolapse quantification points Ba, Bp, and C ⩽0 at 12 months. Results: Sixty-three percent (441/701) of the participants underwent concomitant AR and were older, more often postmenopausal, had previous hysterectomy, and had higher-stage anterior, but not apical prolapse. Anterior anatomic success was marginally but statistically better in the combined group (SSLF and ULS) with concomitant AR (82% vs 80%, P = 0.03). In subanalyses, the improvement in anatomic support with AR was observed only in the SSLF subgroup (81% vs 73%, P = 0.02) and mostly in the SSLF subgroup with higher preoperative stage (74% vs 57%, P = 0.02). Anterior repair did not improve success rates in participants with lower-stage prolapse or undergoing ULS. Overall success rates were similar to anterior anatomic success rates. Participants with higher-stage preoperative anterior prolapse had significantly lower success rates. Conclusions: In the absence of clinical trial data, this analysis suggests an AR should be considered for women with higher-stage prolapse undergoing an SSLF. Preoperative prolapse severity is a strong predictor of poor anatomic outcomes with native tissue vaginal apical surgeries. Abstract : Concomitant anterior repair improves anatomic outcomes in women undergoing sacrospinous ligament suspension for advanced prolapse.